Mechatronics and robotics in the Next Generation EU projects at University of Udine and Free University of Bolzano - Scalera, Lorenzo; Vidoni, Renato; Gasparetto, Alessandro (Anales de Ingeniería Mecánica, 2025)
In this paper we present the role of mechatronics and industrial robotics in the projects funded by the Italian National Recovery and Resilience Plan (PNRR) at University of Udine and Free University of Bolzano in northeastern Italy. The Italian PNRR is part of the Next Generation EU plan, launched by the European Union in response to the COVID-19 pandemic, aiming at promoting strategic investments in digitalization and innovation, ecological transition, and social inclusion. The projects presented in this paper include the Interconnected Nord-Est Innovation (iNEST) Ecosystem, and the Agritech National Center. The activities of the robotics research groups within the iNEST Ecosystem mainly include dynamic modelling and trajectory planning for energy efficiency and safe human-robot collaboration, and design of Digital Twin solutions for efficient simulations and modelling of mechatronic and robotic systems. Furthermore, the Agritech project foresees the development and implementation of mobile robotic systems for monitoring and mapping agricultural fields, as for instance vineyards, as well as the sustainable applications of robotics and mechatronics to forestry management. The expertise gained from this projects will allow University of Udine and Free University of Bolzano to set up other innovative projects also at the international level, and in particular with research groups in Mechatronics and Robotics present in Spanish Universities. Indeed, both University of Udine and the Free University of Bolzano already collaborate with several Spanish institutions for exchange of students and teachers, as well as in the organization of short joint courses (Blended Intensive Program), in the framework of the Erasmus+ program: such collaboration can then be extended to the domain of research and consolidated at the institutional level.